PEMBUATAN BANK SAMPAH PADA UNIT BANK SAMPAH MUTIARA BESTARI SEBAGAI PEMBERDAYAAN MASYARAKAT - Purba, Daris; Ciptoputra, V Ade Arianto; Sari, Asih Purwana; Suratman (ASOSIASI IDEBAHASA KEPRI, 2024)
The government is having difficulty dealing with the waste crisis in Batam and therefore needs help from the community. One way to help is by creating a waste bank in each housing area. This service activity aims to empower the community through the creation of a waste bank unit which is expected to reduce the volume of waste thrown into final disposal sites while empowering the community in the form of generating community income from managing waste. The method of implementing service is through counseling, socialization, implementation, and evaluation. To increase productivity, production materials, and socialization props are provided. Service activities succeeded in increasing production from 136.2 kg per month to 386 kg per month and increasing the waste bank revenue from IDR 290,000 to IDR 750,000 per month.